Possible Roles of Proinflammatory Signaling in Keratinocytes Through Aryl Hydrocarbon Receptor Ligands for the Development of Squamous Cell Carcinoma - Sato, Yota; Fujimura, Taku; Hidaka, Takanori; Lyu, Chunbing; Tanita, Kayo; Matsushita, Shigeto; Yamamoto, Masayuki; Aiba, Setsuya (Frontiers in Immunology, 2020)
Aryl hydrocarbon receptor (AhR) provides a deeper insight into the pathogenesis of cutaneous squamous cell carcinoma (cSCC). AhR ligands, such as 6-formylindolo[3,2-b] carbazole (FICZ), and 7,12-Dimethylbenz[a]anthracene (DMBA), constitute major substrates for the cytochrome P450 (CYP) family, and influence the expression of various cytokine genes, including IL-17 and IL-23-related genes via the AhR. On the other hand, proinflammatory cytokines could drive tumor progression through the TRAF-ERK5 signaling pathway in cSCC. From the above findings, we hypothesized that AhR ligands might enhance the mRNA expression of proinflammatory cytokines via the AhR, leading to the development of cSCC. The purpose of this study was to investigate (1) the immunomodulatory effects of FICZ and DMBA on normal human keratinocytes (NHKCs), focusing on IL-17, and related cytokines/chemokines (IL-23, IL-36γ, and CCL20), (2) the expression of these factors in AhR-dependent pathways using a two-stage chemically induced skin carcinogenesis mouse model, and (3) the expression of these factors in lesion-affected skin in cSCC. Both FICZ and DMBA augmented the expression of CYP1A1, p19, CCL20, and IL-36γ mRNA in NHKCs in vitro. Moreover, the mRNA expression of these proinflammatory factors, as well as IL-17, in mouse cSCC is significantly decreased in the AhR-(fl/fl) Krt5-(Cre) mice compared to wild type mice, leading to a decrease in the number of developed cSCC lesions. Furthermore, CCL20, IL-23, as well as IL-17, are detected in the lesion-affected skin of cSCC patients. Our study demonstrates a possible mechanism for the development of cSCC involving AhR-mediated signaling by epidermal keratinocytes and recruitment of Th17 cells.